Patrimônio e paisagem em Brasília - Alba Nélida de Mendonça Bispo (2022)
This thesis investigates the links between the scales of preservation of the modern city-park and the perspective of safeguarding the landscape adopted in the first cities listed by IPHAN, in 1938, in Minas Gerais. Between modernity and tradition, it focuses on the listed sets of Brasília and Diamantina, since Lucio Costa indicated this city in the interior of Minas Gerais as one of the ingredients of the urban design of Brasília. The research is structured on the approach of Alain Roger (2007) on the double artealization of the landscape carried out “in visu” and “in situ”, because the way we visualize and idealize the places in our imagination conditions the way we model and interfere in the natural and/or built site. The results indicate academic and technical gaps when the term “landscape” is confused with “environment”, so that heritage discourses and practices are limited to criteria of imagery preservation, amidst other socio-spatial, compositional or aesthetic methods and methods. artistic practices in the patrimonialization of landscapes.